Diagnosing Pre-Service Science Teachers’ Multiple Representational Understanding of Chemical Bonding - Rahayu, Dea Santika; Adila, Agista Sintia Dewi; Mustaqimah, Fitriani (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2026)
Chemical bonding is an abstract and conceptually demanding topic because learners must connect symbolic notation, particle-level mechanisms, and visual models. This study aimed to diagnose pre-service science teachers’ multiple representational understanding of chemical bonding using a quantitative descriptive method. Data were collected using a 23-item multiple-choice test on chemical bonding representations. From 43 initial respondents, 41 valid complete responses were analyzed after data screening. Each item was scored dichotomously and analyzed through descriptive statistics, performance categorization, construct-level accuracy, item difficulty, item discrimination, point-biserial correlation, and dominant distractor patterns. The instrument showed high internal consistency, with Cronbach’s alpha/KR-20 of 0.879. The results showed a mean score of 17.20 out of 23, equivalent to 74.76%, indicating generally high performance. Symbolic recognition showed the highest accuracy at 80.49%, followed by representational interpretation at 75.30% and submicroscopic reasoning at 70.46%. Item-level findings revealed difficulties in selecting ionic bonding models, explaining electrostatic attraction, interpreting ionic lattices as extended networks, and recognizing representational equivalence beyond surface features. These findings suggest the need for explicit representational scaffolding in science teacher education.